Blood Levels of Free Fatty Acids and Energy-Rich Phosphates in Patients with Acute Acetic Acid Poisoning Complicated by Toxic Shock - N. A. Sokolova (Общая реаниматология)
Objective: to study the blood levels of free fatty acids (FFA) and adenyl nucleotides in patients with acute acetic acid poisoning (AAAP) complicated with exotoxic shock (ES). Subjects and methods. The study enrolled 33 patients with severe AAAP (with (n=10) and without (n=23) ES), of them there were 5 deaths. The patients’ age was 31.6±11.6 years. A control group comprised 16 healthy individuals. The total level of FFA and the concentration of glycerol were measured in the plasma. Red blood cells were as an object for investigation of ATP, ADP, and AMP. Hearts were morphologically studied in 5 patients died from shock. The data were statistically processed using the Mann-Whitney rank nonparametric tests. The differences were regarded as statistically significant at the achieved significance level of pConclusion. Microscopic studies of the hearts from the deceased patients revealed multiple cardiomyocyte necroses. All the patients with severe AAAP showed a considerably elevated blood level of FFAs with their impaired myocardial utilization and decreased red blood cell ATP and ADP concentrations. The most pronounced changes were found in a group of patients with AAAP and ES. Key words: acetic acid poisoning, exotoxic shock, free fatty acids, energy-rich phosphates.